Application of the solution to the clustering problem with constraints to determine the stability condition of mine slopes (Research, Society and Development, 2023)
This paper presents an application of the Biased Random Key Genetic Algorithm (BRKGA) method to the constrained clustering problem. The solution to this problem returns the separation of a set of data into clusters, such that the members of each cluster are similar to each other, respecting the constraints of the data. The data used are from 88 mine slopes located in different countries around the world. Solving the constrained clustering problem, we seek to determine the stability condition of mine slopes through their geomechanical characteristics. In this context, we hope that the method can be used and applied in small and large mining projects.